Quantum chemical and experimental evaluation of the inhibitory action of two imidazole derivatives on mild steel corrosion in sulphuric acid medium. Issue 11 (November 2019) - Ouakki, M.; Galai, M.; Rbaa, M.; Abousalem, A.S.; Lakhrissi, B.; Rifi, E.H.; Cherkaoui, M.
Abstract: The adsorption and corrosion inhibition properties of two imidazole derivatives namely, 2-(4-chlorophenyl)-1, 4, 5-triphenyl-1H-imidazole (IM-Cl) and 1, 4, 5-triphenyl-2-(p-tolyl)-1H-imidazole (IM-CH3 ) for mild steel in 0.5 M H2 SO4 solution are studiedby electrochemical and computational calculations. The results obtained from the electrochemical methods show that IM-Cl and IM-CH3 imparted high resistance and behave as mixed type inhibitors. Inhibition efficiency (IE %) increases with the increase of inhibitors concentration to attain 96 % and 91% at 10 −3 M of IM-Cl and IM-CH3 respectively. EISdatais analyzed to model the inhibition process through appropriate equivalent circuit model. Thermodynamic and kinetic parameters controlling the adsorption process are calculated and discussed. DFT calculations are carried out at the B3LYP levels of theory with 6-31G (d, p) basis stein gas and aqueous phase for neutral and protonated forms. Quantum chemical calculations section of the study provides enough calculation and discussion on the relationship between corrosion inhibition and global reactivity descriptors. Abstract : Materials chemistry; Electrochemistry; Theoretical chemistry; H2SO4; Corrosion inhibition; DFT; Adsorption; Imidazole; EIS